Mean length of utterance (MLU) in typically-developing 2.5-5.5 year-old Persian-speaking children in Iran - Yalda Kazemi; Alireza Taheri; Faranak Kiyanfar; Meysam Shafie; Robab Eslamifard; Mansoureh Pirmoradian; Zahra Hajgholam Rezaei; Leila Daneshi; Aliyeh Delavari; Majid Zareei; Fatemeh Zarafshan; Fatemeh Falahzadeh; et al. (Vesnu Publications, 2013)
Introduction: Mean length of utterance in morphemes (MLU) is widely used as a general index of language development in pre-school children. Because of insufficient data on Persian language development in Iran, this study examined the MLU of Persian-speaking children and its relation to their in an attempt to help improving clinical decision making. Materials and Methods: This cross-sectional study was conducted on 171 typically-developing children 2.5-5.5 years of age who were recruited from nursery settings of Isfahan, Iran. The sample was selected using a mixed method of sampling and divided into six age groups. After an informal conversation with each child to gauge whether the child appeared to be typically developing in terms of language and cognitive levels, speech therapists played with and tape-recorded them. Each child's MLU was calculated for 75 complete and intelligible utterances longer than one word. The mean and standard deviation of MLU were computed for each age group within six-month intervals. The correlation between age and MLU was also investigated. Results: The children's mean MLU increased between 37-42 and 43-48 months and also between 43-48 and 49-54 months of age. The increase in MLU from the first age group onward was statistically significant. The correlation between age in months and MLU in morphemes was significant, r(171) = 0.47, P < 0.005. Conclusion: The average MLU of the children in this study-and similar studies of Persian-speaking children is much higher than that reported for English-speaking children, and the correlation with age lower; mainly because of morpho-syntactic differences between languages. Age sensitivity of MLU in Persian, however, indicates its capability as a developmental scale for monitoring syntax development in Persian-speaking children which needs to be deeply investigated in relation to Persian language-specific features, either. Keywords: Mean length of utterance, Syntax development, Language development, Pre-school children, Speech therapy